2017
DOI: 10.1371/journal.pone.0189370
|View full text |Cite
|
Sign up to set email alerts
|

High genetic structure and low mitochondrial diversity in bottlenose dolphins of the Archipelago of Bocas del Toro, Panama: A population at risk?

Abstract: The current conservation status of the bottlenose dolphin (Tursiops truncatus) under the IUCN is ‘least concern’. However, in the Caribbean, small and localized populations of the ‘inshore form’ may be at higher risk of extinction than the ‘worldwide distributed form’ due to a combination of factors including small population size, high site fidelity, genetic isolation, and range overlap with human activities. Here, we study the population genetic structure of bottlenose dolphins from the Archipelago of Bocas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 98 publications
(185 reference statements)
1
39
0
2
Order By: Relevance
“…Dolphin Bay is characterized by shallow, clear waters approximately 20 m deep, possessing variable bottom substrate including mud, coral, sea grasses, and mangroves (Kaufmann & Thompson, 2005). Because dolphins use this embayment year-round it is likely an important foraging habitat (May-Collado et al, 2017) where dolphins feed primarily on lowcalorie prey such as striped parrotfish (Scarus isiri) and dwarf round herring (Jenkinsia lamprotaenia) (Barragán- Barrera et al, 2019). Since monitoring efforts began in 2004, high sighting rates of mother-calf pairs (including two neonates observed in this study) suggest Dolphin Bay may also serve as critical habitat for females with dependent offspring.…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…Dolphin Bay is characterized by shallow, clear waters approximately 20 m deep, possessing variable bottom substrate including mud, coral, sea grasses, and mangroves (Kaufmann & Thompson, 2005). Because dolphins use this embayment year-round it is likely an important foraging habitat (May-Collado et al, 2017) where dolphins feed primarily on lowcalorie prey such as striped parrotfish (Scarus isiri) and dwarf round herring (Jenkinsia lamprotaenia) (Barragán- Barrera et al, 2019). Since monitoring efforts began in 2004, high sighting rates of mother-calf pairs (including two neonates observed in this study) suggest Dolphin Bay may also serve as critical habitat for females with dependent offspring.…”
Section: Study Areamentioning
confidence: 99%
“…A recent study found that resident females possess a relatively long calving cycle (~62 months) and a high calf mortality rate (46%) (May-Collado et al, 2019). Additionally, nuclear and mitochondrial DNA analyses indicate this population is isolated from others in the Caribbean, including the neighboring population of bottlenose dolphins in Costa Rica located 35 km away from the Bocas del Toro archipelago (Barragán- Barrera et al, 2017). Because the small dolphin community of Dolphin Bay shows such high site fidelity, they have become the main target for dolphin watching activities in the area, resulting in the largest dolphin watching fleet in Panama (May-Collado et al, 2012, 2019.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations